Forensic Linguistics as a Scientific Study in the Field of Law and Justice - Yuliastuti, Eko; Aini, Miza Rahmatika; Sukaito, Yuno (JOSAR (Journal of Students Academic Research), 2024)
Legal science has various connections with other branches of science. One of them is Forensic Linguistics. So it can be said that legal science is related to the branch of Linguistics. This connection can be seen and studied in the process of investigating and determining suspects. In this case, the researcher took data from the BAP carried out by the Blitar City Police. In the investigation BAP there is a linguistic study which can later play an important role in determining the legal process that the suspect will face. The research was conducted at the Blitar City Police Criminal Investigation Unit. Data obtained from recording and recording BAP. After the data was recorded, it was analyzed using qualitative descriptive methods. From the data obtained, linguistics can help the police in conducting research on suspects.